Using Fly Ash And Bottom Ash Boiler Of Palm Oil Factories As Adsorbents For Adsorption Of Color In Artificial Liquid Waste - Juang Jaya Putra Telaumbanua (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2020)
This study aims to determine the ability of battom ash and fly ash in adsorbing artificial wastewater dye (PtCo) and chemical oxygen demand (COD) with three variations of adsorbent used in adsorption column. This research begins with the process of washing, drying and sieving adsorbent. Then proceed with the activation process of adsorbent using HCl 1 M which is heated at 90 0C for 1 hour accompanied by stirring. The adsorption system used is continuous (column) with up-flow flow pattern and using the pump to provide pressure so that the influent can pass through the adsorbent contained in the column. The characteristic analysis of adsorbent was done on moisture content, ash content, and iodine absorption. The highest moisture content and ash content obtained were 0.6% with fly ash adsorbent before activation and 0.285% with fly ash adsorbent after activation. Compared with SNI 06-3730-95 has been appropriate, while the iodine drainage from bottom ash was 35.38 mg/g and fly ash of 50.76 mg/g and none meet SNI 06-3730- 95 of 750 mg/g. The highest efficiency results in dye and COD were found in adsorption column with fly ash adsorbent with color value of 96.96% and COD concentration of 83.26%, followed by stratified columns with combined adsorbent between battom ash and fly ash with color values of 53 , 93% and COD of 62.82%, and adsorbent by using battom ash efficiency of highest color value of 53.03% and COD of 71.08%. The highest adsorption capacity was obtained by using adsorption column with battom ash and fly ash (BF) adsorbent of 8.42 mg/g, followed by fly ash (FA) of 7.53 mg/g and battom ash (BA) of 7, 37 mg/g.